CORRUPTION AS A CULTURAL AND ETHNIC PHENOMENON - Isomiddinov Yunusjon Yusubboevich (Journals Park Publishing, 2023)
The topic of corruption has been one of the most attractive for researchers of the widest range during the last decades. The fact is that it is an extremely paradoxical phenomenon, since the theoretical degree of its study, as well as the intensity of practical measures to combat it do not contribute to its eradication or even reduction of its manifestations. At the same time, corruption continues to have an extremely negative impact on the social life of society and its everyday reality.